Description of a new species of Anagyrus Howard (Hymenoptera: Chalcidoidea: Encyrtidae), a promising biological control agent of the invasive Madeira mealybug, Phenacoccus madeirensis Green (Hemiptera: Sternorrhyncha: Pseudococcidae) - Rameshkumar, A.; Noyes, J. S.; Poorani, J.; Chong, J. H. (Zootaxa, 2013)
Anagyrus amnestos sp. n. (Hymenoptera: Encyrtidae), a promising parasitoid of the invasive Madeira mealybug, Phenacoccus madeirensis Green (Hemiptera: Pseudococcidae), is described based on material collected from India. This parasitoid was identified as Anagyrus sp. nov. nr. sinope Noyes & Menezes in recent literature, and was initially collected in Georgia, USA. It was found to be a specific parasitoid of the Madeira mealybug and its biological attributes and potential as a biological control agent of this pest were studied. In what appears to be a case of fortuitous introduction, we detected this parasitoid in large numbers on Madeira mealybugs from the southern Indian state of Karnataka, where the mealybug is a recently introduced invasive pest. In view of its economic importance as a potential biological control agent of the Madeira mealybug, it is formally described and illustrated here. Comparative accounts of the new species vis-a-vis its close relatives in India and the Americas are provided.